WhatsApp Groups as a Team-Based Learning Model for Ayurveda Undergraduate Students - Gaurav Sawarkar; Punam Sawarkar (Journal of Pharmacy and Bioallied Sciences)
Team-based learning (TBL) involves students working together to solve problems or complete tasks. Active learning, collaboration, and critical thinking are promoted. TBL uses pre-class preparation, in-class team activities, and evaluations to improve course comprehension and application in a dynamic learning environment. Organise WhatsApp groups for TBL in Ayurveda courses by assigning facilitator, recorder, and timekeeper roles. Group discussion, case studies, sharing resources, and scheduling in-depth discussions to improve TBL by encouraging active engagement, good communication, and timely task completion. Faculty or moderators monitor WhatsApp groups, enforce rules, and facilitate discussions. WhatsApp group collaborative learning may improve academic performance because students gain peer interactions and different perspectives. It enhances learning by encouraging active participation and comprehension. Communication, teamwork, and critical thinking are taught to help students succeed in their careers.